Artificial intelligence in microbial natural product drug discovery: current and emerging role - SahayaSheela, Vinodh J.; Lankadasari, Manendra B.; Dan, Vipin Mohan; Dastager, Syed G.; Pandian, Ganesh N.; Sugiyama, Hiroshi (Natural Product Reports, 2022)
Covering: up to the end of 2022 Microorganisms are exceptional sources of a wide array of unique natural products and play a significant role in drug discovery. During the golden era, several life-saving antibiotics and anticancer agents were isolated from microbes; moreover, they are still widely used. However, difficulties in the isolation methods and repeated discoveries of the same molecules have caused a setback in the past. Artificial intelligence (AI) has had a profound impact on various research fields, and its application allows the effective performance of data analyses and predictions. With the advances in omics, it is possible to obtain a wealth of information for the identification, isolation, and target prediction of secondary metabolites. In this review, we discuss drug discovery based on natural products from microorganisms with the help of AI and machine learning.